2009
DOI: 10.1097/gco.0b013e32832aee96
|View full text |Cite
|
Sign up to set email alerts
|

The impact of body mass index on assisted reproduction

Abstract: Obesity has a negative impact on the outcomes of assisted reproductive techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
1
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(39 citation statements)
references
References 75 publications
(118 reference statements)
0
36
1
2
Order By: Relevance
“…Endometrial receptivity may be impaired in obese women. These mechanisms may be responsible for a decrease in implantation and pregnancy rates as well as an increase in miscarriage rate, yielding to a poorer outcome in obese women in assisted reproduction [12,13]. The mechanism underlying the inverse relationship between obesity and AMH is not entirely clear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endometrial receptivity may be impaired in obese women. These mechanisms may be responsible for a decrease in implantation and pregnancy rates as well as an increase in miscarriage rate, yielding to a poorer outcome in obese women in assisted reproduction [12,13]. The mechanism underlying the inverse relationship between obesity and AMH is not entirely clear.…”
Section: Discussionmentioning
confidence: 99%
“…There is abundant evidence that increased body mass index (BMI) has a significant adverse effect on pregnancy and miscarriage rates in women seeking to become pregnant naturally [12,13]. Attention has been paid to the causes of poor fertility outcomes in overweight women, seeking to determine whether these outcomes are due to an ovarian or endometrial effect [13].…”
Section: Introductionmentioning
confidence: 99%
“…In Bellver et al, 2010, this result was also found with p value of 0.001. In Erel et al, 2009 review, several articles were evaluated. Some have shown that higher dose it is necessary, while in others not.…”
Section: Dose Of Gonadotropinsmentioning
confidence: 99%
“…Obese may be further divided into classes: Class I with BMI 30 to 34.9 kg/m², Class II 35 to 39.9 kg/m² and class III when greater than or equal to 40 kg/m². In the last decade, the global trend shows an increase of about 40% of overweight and obesity in women of reproductive age (Erel et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The subfertility in obese women is partly ascribed to the complete absence or reduced frequency of ovulation (53). Obesity has been reported to have a negative impact on assisted reproduction techniques because it adversely affects the duration of stimulation of the ovaries, fertilization rate, quality, and some oocytes and embryos, the rate of embryo transfer, and pregnancy rates (54). Consequently, obese women have been shown to require higher doses of gonadotropins and longer durations of ovarian stimulation.…”
Section: Ovarian Functionmentioning
confidence: 99%